Vardažodžių galūnių ir kamienų akcentinės galios nustatymo tvarka - Pakerys, Antanas (Kalbotyra, 2000)
The article analyses accentual relations between inflexions and stems of declinable words from a morphonological standpoint. The following concept, are given a brief description: accentual strength and weakness of morphemes, prosodic features of the last syllable of stems and attractability of inflexions. Morphemes of disyllabic declinable words are described in the following order: 1) weak non-attractable inflexion, 2) weak attractable inflexion, 3) weak stem with falling accent, 4) weak stem with non-falling accent, 5) strong stem with falling accent, 6) strong stem with non-falling accent, 7) strong non-attractable inflexion, 8) strong attractable inflexion. The definitions obey the rule that any latter definition has to be based on the former one. There are three rules determining which morpheme gets the stress: 1) the rule of attractability, 2) the rule of equal power, 3) the rule of larger power. The rule of inflexion attractability has priority over the other two. It is always to be applied first. The same definitions and rules could be applied in a slightly modified form to polysyllabic words as well. Finally, accentual peculiarities of numerals and pronouns are discussed.